PENGARUH PROGRAM GERAKAN LITERASI SEKOLAH TERHADAP KETERAMPILAN MEMBACA TEKS BERITA - Revani Rusdiawati; Rini Agustina; Al Ashadi Alimin (Proceedings of the International Conference on Literacy and Education, 2022)
This study aims to determine the effect of the implementation of the school literacy movement program on reading text news skills. The method used is pre-experimental design, the research design used is one group pre-test post-test design. Based on the results of calculations using the t-test, the value of tcount is 21.07 and t table (ɑ = 5%, db = n-35 = 34) of 1.6905. Because tcount (21.07)> t table (1.6905) this means that it must be accepted, so it can be agreed on the application of the school literacy movement program on the report text reading skill.